Efektivitas Program Cash For Work (CFW) Sebagai Upaya Pemerintah Dalam Mitigasi Pandemi Covid-19 (Studi Pada Kelurahan Kebonsari Wetan Kecamatan Kanigaran Kota Probolinggo): (Studi Pada Kelurahan Kebonsari Wetan Kecamatan Kanigaran Kota Probolinggo) - Siti Marwiyah; Andhi Rahmadi; Riza Aisyah (Administratio, 2022)
The issue of layoffs is currently an important issue in the sector, marked by figures that have increased significantly due to the COVID-19 pandemic. Through the cash for work program, mitigation efforts are carried out by the Indonesian government to push back the pace of the community's economy. This paper intends to examine the effectiveness of the cash for work program during the COVID-19 pandemic in Kebonsari Wetan Village, Kanigaran District, Probolinggo City, which is one of the kelurahan that has the opportunity to implement the program. This study used descriptive qualitative method. The selection of informants was chosen intentionally which was considered to be about the things to be studied, took data from sources that were considered relevant according to the problems and themes raised, so as to produce reliable data and determine the accuracy of the research results. This study uses the theory of effectiveness according to Sutrisno (in Wulandari 2018: 6), namely program understanding, timeliness, accuracy of targets, goals and changes. This research feels that in terms of program understanding indicators, targeting, timeliness, achieving a sense of effectiveness, but in real change it is less effective because this program is only temporary so that the community will tend to interfere when the program is completed. The form of mitigation in the cash for work program has fulfilled several requirements, namely the involvement of various parties, the principle of the main priority being vulnerable groups. The implication of the cash for work program is that it has a good impact in helping to increase people's income and settlement problems in the Kebonsari Wetan Village area